Transformation of Phraseological Units in the English-Language Press and Their Translation into Russian - Shukhratova Mukhlisakhon Shukhratjon qizi (Researchparks Publishing, 2022)
The English language has a thousand-year history. During this time, it has accumulated a large number of expressions that people considered successful, well-aimed and beautiful. This is how a special layer of the language arose - phraseology, a set of set expressions that have a special meaning. A good knowledge of the language, including English, is impossible without knowledge of its phraseology. Phraseological units have become an integral part of journalism and the language of newspapers. But if the issue concerning the translation of phraseological units is defined to some extent, then the problem of translating phraseological transformations remains largely controversial and still poorly understood.